Classification based on mutations of TERT promoter and IDH characterizes subtypes in grade II/III gliomas - Yang, Pei (Neuro Oncol, 2016)
BACKGROUND: Grade II and III gliomas have variable clinical behaviors, showing the distinct molecular genetic alterations from glioblastoma (GBM), many of which eventually transform into more aggressive tumors. Since the classifications of grade II/III gliomas based on the genetic alterations have been recently emerging, it is now a trend to include molecular data into the standard diagnostic algorithm of glioma. METHODS: Here we sequenced TERT promoter mutational status (TERTp-mut) in the DNA of 377 grade II/III gliomas and analyzed the clinical factors, molecular aberrations, and transcriptome profiles. RESULTS: We found that TERTp-mut occurred in 145 of 377 grade II and III gliomas (38.5%), mutually exclusive with a TP53 mutation (TP53-mut; P < .001) and coincident with a 1p/19q co-deletion (P = .002). TERTp-mut was an independent predictive factor of a good prognosis in all patients (P = .048). It has been an independent factor associated with a good outcome in the IDH mutation (IDH-mut) subgroup (P = .018), but it has also been associated with a poor outcome in the IDH wild-type (IDH-wt) subgroup (P = .049). Combining TERTp-mut and IDH-mut allowed the grade II/III malignancies to be reclassified into IDH-mut/TERTp-mut, IDH-mut only, TERTp-mut only, and IDH-wt/TERTp-wt. 1p/19q co-deletion, TP53-muts, Ki-67 expression differences, and p-MET expression differences characterized IDH-mut/TERTp-mut, IDH-mut only, TERTp-mut only, and IDH-wt/TERTp-wt subtypes, respectively. CONCLUSIONS: Our results showed that TERTp-mut combined with IDH-mut allowed simple classification of grade II/III gliomas for stratifying patients and clarifying diagnostic accuracy by supplementing standard histopathological criteria.